Pembelajaran Kosakata Bahasa Indonesia Bagi Penutur Asing di Sekolah Dasar Canberra Australia - Miftahulkhairah Anwar; Iqbal Ifada; Liliana Muliastuti; Eva Leiliyanti; Muhammad Ariefin (CV. Global Cendekia Inti, 2026)
The method employed in this program was an interdisciplinary approach. The activities encompassed program planning, implementation mechanisms, activity stages, evaluation, sustainability, and expected outcomes. The training involved several partners in Canberra, namely: (1) the Indonesian Education and Cultural Attaché in Canberra, (2) teachers from Trinity Christian School, and (3) teachers from Burgmann Anglican School. The implementation of the snakes-and-ladders gamification at Trinity Christian School and Burgmann Anglican School demonstrated that this game can serve as an effective medium for enhancing students’ ability to recognize and understand Indonesian vocabulary. This program has made a positive contribution to the development of the Indonesian language abroad. This initiative is aligned with the mandate of Law No. 24 of 2009 concerning the internationalization of the Indonesian language, which emphasizes the importance of promoting and teaching Indonesian across countries. The success of this program represents a significant step toward strengthening international relations, as well as enhancing global understanding and appreciation of Indonesian culture.